Quality of Service Packet Loss pada Sistem Home Monitoring Water Flow Berbasis Internet of Things - Pratama, Andree Fajar; Baqaruzi, Syamsyarief; Muhtar, Ali (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
The wasteful behavior of clean water causes more and more people to lose access to clean water. The use of water in households so far is still very difficult to manage in using water effectively. Clean water scarcity is a situation when there is a shortage of water to meet human needs. This study built a Home Water Flow Monitoring (HEROIG) system based on the Internet of Things (IoT) to monitor and control water use at home. The hardware uses NodeMCU as a microcontroller and sends the sensing results of the water flow by the water flow sensor which will be sent to the cloud server. Control can be done through the HEROIG android application which has been created and integrated with the IoT system which must work in a good network connection. Testing the quality of the network connection or Quality of Services (QoS), especially packet loss, uses two parameters, namely time and distance. The results of testing the time parameter packet loss by testing once in six seconds in one minute have an average packet loss value of 1.13%, then for testing the distance parameter with the difference of each distance is four meters has an average packet loss value of 0.15% . The test results show that the quality of sending sensor data to the cloud server has a very good category of QoS packet loss parameters, because it has a packet loss value <3%.